CLASSICAL TRAJECTORY CALCULATIONS OF NONLINEAR SPUTTERING - SICL4 SPUTTERING OF A CU(001) SURFACE USING ABINITIO POTENTIALS - Broomfield, K; Stansfield, R; Clary, D (1990)
Classical trajectory calculations are carried out on SiCl4 sputtering of a Cu(001) surface. The repulsive Cusingle bondSi and Cusingle bondCl interaction potentials are calculated using ab initio electronic structure theory. At energies of 120 eV or greater, the calculated sputtering yields are found to be greater than the sum of the component atomic sputtering yields. This effect cannot be explained by a thermal spike such as has been invoked to explain nonlinear sputtering at higher energies. Examination of individual trajectories suggest that different sputtering mechanisms become operational as the kinetic energy of the incident molecule is increased. The observed enhancement of the molecular sputtering yield can be explained by the overlap of the individual atomic collision cascades. © 1990 Elsevier Science Publishers B.V. (North-Holland).